Effects of body size phenotype on sleep quality in middle-aged Korean men - Ji Young Kim; Youngran Yang; Sung-Heui Bae (Journal of Men's Health, 2022)
Background: Research on body size phenotype according to metabolic syndrome and obesity is being actively conducted. Quality of sleep can vary depending on the body size phenotype. This study aimed to investigate the effects of body size phenotype on sleep quality in middle-aged Korean men. Methods: This study used secondary data analysis from a community-based cohort of the Korean Genome and Epidemiology Study (KoGES). Using BMI and metabolic health status, among 3675 men aged between 40 and 65 years, body size phenotypes were classified as follows: metabolically healthy normal weight (MHNW) (50.8%), metabolically healthy obesity (MHO) (32.5%), metabolically abnormal obesity (MAO) (12.7%), and metabolically abnormal but normal weight (MANW) (4.0%). Results: MANW men had the most prolonged sleep duration (more than 7 hours), and MHO men had the shortest sleep duration. The degree of difficulty falling back to sleep after waking in MHO men was 0.76 times that of MHNW men (p = 0.02). Conclusions: Sleep duration and difficulties falling back to sleep were independently associated with body size phenotype in middle-aged men after adjusting for confounding factors. Health professionals and officials in labor departments may use the results of this study to improve the quality of sleep and ultimately help with productivity in the workplace.